THE PROBLEMS OF OBTAINING AND PROCESSING DNA SAMPLES IN CRIMINAL PROCEEDINGS - Lieljuksis, Aldis (Administrative and Criminal Justice, 2016)
The article deals with the issue raised in the society regarding constitutional complaint a submitted to the Constitutional Court against the national DNA database and the compliance of the legal norms with Section 96 of the Satversme. The author of the article writes about the issues related to the legal framework of DNA and biometric data sampling from suspects in the context of the EP Resolution No. 2008/615 / JHA, the requirements of the ECHR and the Estonian Criminal procedure regulation. In conclusion, the author is of the opinion that the current DNA sampling legislation does not provide many options for process facilitator and DNA samples must be obtained from all suspected persons to whom such status is applied regardless of the qualification of the offence and the need for criminal proceedings.